The state of apprenticeship in 2010: international comparisons - Australia, Austria, England, France, Germany, Ireland, Sweden, Switzerland - Steedman, Hilary (London, 2010)
"Forward by Sir Roy Gardner (Chairman, Compass Group plc; Chairman, Apprenticeship Ambassadors Network) August 2010: I am pleased to commend this report, commissioned by the Apprenticeship Ambassadors Network, of which I am Chairman. The Network is a group of senior business leaders committed to the expansion and development of Apprenticeships.